Some Psychological Impacts on Judging in Criminal Cases within the Supreme Court of Cassation of the Republic of Serbia - Avramović, Dragutin (NBP. Nauka, bezbednosti, policija, 2020)
Following hypothesis of Andrew Watson, American professor of Psychiatry and Law, the author analyses certain psychological impacts on behavior of judges and examines relation between their idiosyncrasies and their judicial decisions. The survey encompasses judges of Criminal Department of the Supreme Court of Cassation of the Republic of Serbia and, also, for comparative reasons, judges of Criminal Department of the First Basic Court in Belgrade. Considering main issues there is no great discrepancy between answers given by judges of the Supreme Court and of the Basic Court. Most responses of Serbian judges deviate from Watson`s conclusions, namely: they do not admit that they feel frustrated due to heavy caseloads, the significant majority of judges are reluctant to acknowledge their prejudices and influence of biases on their ruling, the significant majority of judges are not burdened with the idea of possible misuse of their discretion, they nearly unanimously deny that public opinion and media pressure affect their rulings, etc. Generally, judges in Serbia are not willing to admit that they cannot always overcome their own subjectivities.
Keywords: Psychoanalytic Jurisprudence, Judicial Discretion, American Legal Realism, Jerome Frank, Andrew Watson